Mediated Exhibitionism: The Naked Body in Performance and Virtual Space. - Jones, Matthew T. (Sexuality & Culture, 2010)
Mediated exhibitionism is the phenomenon of amateur performers exposing their nude bodies on the Internet, and includes the exchange of nude images by email, text message, webcam, electronic bulletin board, and other means of digital communication. Although mediated exhibitionism has its foundation in live performance and traditional media forms, its potential as a means for broadening the aesthetics of the body and offering a form of resistance to social control is magnified by the interactive quality of the Internet. Conversely, new aesthetic ideals have been established and resistance to social control has been challenged by the very technology which made resistance possible. A series of websites catering to mediated exhibitionism were investigated.